Implementation Role Of Notary Deed Incorporation Of Foundation Making Based On Act No. 28 Of 2004 Regarding The Foundation In The Jepara District - Kanzu Khirzul Yaman; Tasmo Tasmo; Amin Purnawan (Jurnal Akta, 2019)
The purpose of this study was to: 1) To determine the role of the Implementation of the notary in the deed establishment of the Foundation under Act No. 28 of 2004 on the foundation of Jepara. 2) To know the difficulties and Solutions faced a notary in the deed establishment of the Foundation under Act No. 28 of 2004 on the foundation of Jepara.Method approach used in this research is a normative juridical approach. Specifications descriptive analytical research. Types and sources of data using secondary data and primary data as well as the use of primary legal materials, secondary law and tertiary legal materials. The collection of data through library research and field study. Qualitative data analysis and deductive.Based on the results of data analysis concluded that: 1) The role of the notary in the deed establishment of the Foundation under Act No. 28 of 2004 on the foundation of Jepara includes three important things, namely, to explain the terms of the deed establishing the foundation to the founder of the foundation, make certificates of establishment, then submit the ratification to the Minister of Justice and Human Rights. 2) Barriers and Solutions encountered in the manufacturing notary deed of incorporation of the Foundation under Act No. 28 of 2004 on the foundation of Jepara is in the maintenance of the terms of the deed establishing the foundation has not completed such as TIN foundations as well as the identity of the parties is not an e-ID card, the solution is certainly advise coaches / administrators to quickly gather the requirements in the manufacture of its founding act.Keywords: Implementation; Notary Deed; Role of Establishment Foundation